Research-based flow cytometry assays for pathogenic assessment in the human B-cell biology of gene variants revealed in the diagnosis of inborn errors of immunity: a Bruton’s tyrosine kinase case-study - del Pino-Molina, L.; Bravo Gallego, L. Y.; Soto Serrano, Y.; Reche Yebra, K.; Marty Lobo, J.; González Martínez, B.; Bravo García-Morato, M.; Rodríguez Pena, R.; van der Burg, M.; López Granados, E. (Frontiers in Immunology, 2023)
Inborn errors of immunity (IEI) are an expanding group of rare diseases whose field has been boosted by next-generation sequencing (NGS), revealing several new entities, accelerating routine diagnoses, expanding the number of atypical presentations and generating uncertainties regarding the pathogenic relevance of several novel variants. Research laboratories that diagnose and provide support for IEI require accurate, reproducible and sustainable phenotypic, cellular and molecular functional assays to explore the pathogenic consequences of human leukocyte gene variants and contribute to their assessment. We have implemented a set of advanced flow cytometry-based assays to better dissect human B-cell biology in a translational research laboratory. We illustrate the utility of these techniques for the in-depth characterization of a novel (c.1685G>A, p.R562Q) de novo gene variant predicted as probably pathogenic but with no previous insights into the protein and cellular effects, located in the tyrosine kinase domain of the Bruton’s tyrosine kinase (BTK) gene, in an apparently healthy 14-year-old male patient referred to our clinic for an incidental finding of low immunoglobulin (Ig) M levels with no history of recurrent infections. A phenotypic analysis of bone marrow (BM) revealed a slightly high percentage of pre-B-I subset in BM, with no blockage at this stage, as typically observed in classical X-linked agammaglobulinemia (XLA) patients. The phenotypic analysis in peripheral blood also revealed reduced absolute numbers of B cells, all pre-germinal center maturation stages, together with reduced but detectable numbers of different memory and plasma cell isotypes. The R562Q variant allows Btk expression and normal activation of anti-IgM-induced phosphorylation of Y551 but diminished autophosphorylation at Y223 after anti IgM and CXCL12 stimulation. Lastly, we explored the potential impact of the variant protein for downstream Btk signaling in B cells. Within the canonical nuclear factor kappa B (NF-κB) activation pathway, normal IκBα degradation occurs after CD40L stimulation in patient and control cells. In contrast, disturbed IκBα degradation and reduced calcium ion (Ca2+) influx occurs on anti-IgM stimulation in the patient’s B cells, suggesting an enzymatic impairment of the mutated tyrosine kinase domain.